PENGARUH MEDIA SMART PARENTING TERHADAP PENGETAHUAN ORANG TUA MENGENAI RESILIENSI ANAK USIA DINI - Ainama Nafisa Putri; Ria Novianti; Daviq Chairilsyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article is based on the lack of parents’ knowledge to create a pleasant and exciting atmosphere for children, the lack of parents’ knowledge to make children feel unpressured by a sudden change, the lack of parents’ knowledge on children’s perceptions of risk and fears, and the lack of parents’ knowledge to educate the children when the children were getting a failure. Hence, the research in this article is aimed to find out the effect of smart parenting media on parents' knowledge regarding resilience for 5–6 years old children. The research used a quantitative research approach with experimental research. The population of the research involved 30 parents and the sample used was 30 parents who have children aged 5–6 years at Pembina Kindergarten Tempuling in Indragiri Hilir. The data collection technique was used through a true-false objective test. The results showed that there was an effect of the use of smart parenting media on parents' knowledge regarding children's resilience. It can be seen from the results of scores and percentages from the pre-test to the post-test. Thus, there is an effect of using smart parenting media on parents' knowledge regarding the resilience of children aged 5–6 years.